Simulasi riak air dengan menggunakan teknik B-Spline - Raima Hassim (2014)
Water simulation is one of the popular topic in the field of computer graphics. There are many techniques that have been proposed including particle techniques, grid-based method and procedural method. Every techniques have its own formula to produce a realistic simulation. Offline rendering able to produce a realistic simulation but the computational cost become very high when the volume of water is high. This project will focused on the water ripples simulation. A prototype of water ripples simulation has been produced by using B-Spline techniques. In general, this technique will produce a curve as a representation of a water ripples simulation by using the generated curve from B-Spline techniques. The surface of water ripples will be simulated by using the function in openGL library. Based on the memory experiments, the memory usage of the running simulation is 13,346 KB only. The total number of frame per second recorded is low and it is indicate that the computation is Significantly low.